Program Pemberdayaan Perempuan Berkelanjutan di Desa Gemel Kabupaten Lombok Tengah - Aldi Gumuruh Wicaksono; Sekar Arrum Permata; Abdul Rahman (Universitas Hamzanwadi, 2022)
NTB has a high number of cases of early marriage, reaching 56.07% in 2018-2019. To support program independence and women's competitiveness in Gemel Village, Central Lombok District, the community established a Women's Empowerment School as the Head of the Family. This study aims to determine the inconsistency of sustainable women's empowerment programs in Gemel Village, Central Lombok Regency; know the community's efforts to overcome program inconsistencies; and explain innovations to support sustainable women's empowerment programs at PEKKA schools in Gemel Village, Central Lombok Regency. This study uses a descriptive method with an inductive approach. The results of the study indicate that there are women's empowerment programs that are unsustainable or inconsistent due to the cessation of assistance from the government or partnership projects between the governments of Indonesia and Australia. Regions to be involved in sustainable women empowerment. The innovation has been made in developing a PEKKA-friendly website for outreach and information with PEKKA stakeholders and the government.